2018
DOI: 10.29313/gmhc.v6i3.2897
|View full text |Cite
|
Sign up to set email alerts
|

Reproductive Health Game (KEPO Game) to the Self-Concept and Adolescent Reproductive Health Motivation

Abstract: The problem of adolescent reproductive health has not been adequately addressed, although there have been many tried attempts both formally and informally. Adolescents aged 12-15 years old are suitable for early reproductive health education, so the needed media that suits their needs and developments. Reproductive health/kesehatan reproduksi (KEPO) game contains information about reproductive health and moral messages in the formation of self-concept, healthy reproduction, health motivation, and responsibilit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
2
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 20 publications
0
2
0
2
Order By: Relevance
“…anaemia [29]. The application of the Reproductive Health Educational Game (KEPO) by Damayanti et al (2019) also shows results in increasing motivation for Reproductive Health [30]. From the collective studies above showed the similar results were the implementation of game innovations on educations made the learning process become more fun, more effective and more efficient, these innovations will be very useful to develop educational curriculum at formal or informal education in future.…”
Section: Discussionmentioning
confidence: 99%
“…anaemia [29]. The application of the Reproductive Health Educational Game (KEPO) by Damayanti et al (2019) also shows results in increasing motivation for Reproductive Health [30]. From the collective studies above showed the similar results were the implementation of game innovations on educations made the learning process become more fun, more effective and more efficient, these innovations will be very useful to develop educational curriculum at formal or informal education in future.…”
Section: Discussionmentioning
confidence: 99%
“…Knowledge is needed as support in growing self-confidence as well as attitudes and behavior every day, so knowledge is a fact that supports one's attitudes. Knowledge is one of the factors that influence health behavior [14].…”
Section: Discussionmentioning
confidence: 99%
“…Perbaikan lain yang perlu diperhatikan adalah perlu adanya sistem peringatan dini kehamilan yang terintegrasi dalam aplikasi sehingga dapat memudahkan monitoring pada ibu hamil. Perkembangan teknologi yang semakin cepat juga menjadikan masyarakat menginginkan layanan kesehatan yang mudah diakses (Damayanti, 2018). Salah satu yang dapat dimanfaatkan adalah media aplikasi yang dapat dibuka melalui smartphone.…”
Section: Pendahuluanunclassified